Immunolocalization of SP22 (Park7) on the human sperm membrane is indicative of live birth - Gary R Klinefelter; Michael P Diamond; Stephen A Krawetz (Reproduction and Fertility)
With the decline in sperm quality over the recent decades, there is little doubt that the decreased efficiency of spermatogenesis in men reflects their increasing susceptibility to environmental and pharmaceutical exposures that can compromise male fecundity. More than twenty years have passed since we discovered a novel sperm membrane protein (SP22) derived from the Park7 gene that is highly correlated with the fertility of rat sperm exposed to epididymal toxicants. We subsequently discovered that SP22 originates in the testis and is also compromised during exposure to testicular toxicants. Recently, we were given an opportunity to test the hypothesis that human sperm may also have reduced fertility when levels of SP22 are significantly decreased. Using a recombinant antibody to the functional epitope of SP22, we compared sperm from donors who achieved a live birth to donors who were not able to achieve a pregnancy. Sperm SP22 was significantly reduced in a group of donors not able to achieve a pregnancy. A similar reduction in birth was also observed among specific Park7 and SP22 exons when a group of donors unable to achieve a pregnancy was compared to the live birth donors. To our knowledge, this is the first demonstration that SP22 expression can be compromised in men with reduced fertility. This opens the door to incorporating SP22 analyses in future epidemiology studies and developing over-the-counter testing for men with suspected male infertility.